Estudos ecofisiológicos em arbóreas do manguezal do Rio Mucuri - BA - Rocha, Andréa Campos (2008)
The present study investigated the influence of the Mucuri river flow fluctuation on the mineral composition of leaves and sediments of Rhizophora mangle, Laguncularia racemosa and Avicennia germinans and the physicochemical properties of their respective rizospheres. Three stations were demarcated in a monospecific area and ten trees were monitored, five in the riverside region and five in the bay region. The macronutrient and micronutrient concentrations of the sediment and leaves, and the OM content, pH, and granulometric fractions were determined. The experimental design was completely randomized and used factorial (3x2x2), involving three species, two physiographic regions (riverside and bay), and two seasons of the year (higher and lower flow of the river). Granulometry varied among the three species analyzed but not in relation to the flow of the river, showing that the architecture of each species is crucial in the capture and stabilization of sediments. The physicochemical parameters and the levels of nutrients from rizospheres of the three species also showed predominant spatial variation (between the two regions analyzed) showing that the relation between the sediment and plants is extremely important. The pH of the sediment and water and the sediment temperature were higher in the high flow month, showing that the relationship between hydrological conditions and time of the year is very close. The high flow season concentrated a low number of sediments, macronutrients, and micronutrients showing a dilution effect. Because of the physiographic features, the basin and riverside regions showed, respectively, the highest values of macronutrients and micronutrients. Leaf macronutrient and micronutrient concentrations varied with the seasons of higher and lower river flow, and the dry period presented the highest levels, showing that the relationship between climatic factors and the sediments is important in the leaf chemical composition of these species. The results described in 26 this paper showed that the physicochemical parameters and the concentrations of nutrients from leaves and sediment have seasonal variability and respond to different environmental factors. This knowledge is very important to the understanding of the physicochemical processes of the mangroves.